Allocentric spatial memory following anterior temporal lobectomy: A comparison between active and sedentary epileptic adults - Cotton, Sarah (Department of Psychology, 2014)
The association between neural activity of the left hemisphere hippocampal region and verbal memory has been well established. Similarly, neuropsychological outcomes following left anterior temporal lobectomy (ATL) have been well documented, with deficits in the ability to learn new verbally encoded material consistently displayed. However, the association between non-verbal memory and functioning of the right hemisphere hippocampal region and, consequently, neuropsychological outcomes following right ATL, remains an area of debate. Moreover, relatively new evidence suggests that physical activity could improve overall hippocampal function (McCloskey, 2003). Therefore, the aim of the present study was to investigate spatial cognition in patients with intractable epilepsy and also to establish whether physical activity levels of these patients, i.e. active versus sedentary, had an effect on neuropsychological functioning. Spatial and verbal cognition were assessed in three groups: a pre-surgical (awaiting ATL) group, a post-surgical (following ATL) group and a healthy control group. Physical activity levels of all participants were established and left-sided damage and right-sided damage patient groups were divided into those with moderate-to-high activity levels and those with low activity levels. Results showed that on tests of spatial cognition, patients with right-sided damage tended to show more deficits than patients with left-sided damage when assessed using experimental tasks. However, no group differences were found when using standard clinical tests for assessment. On tests of verbal memory, patients with left-sided damage displayed more deficits than patients with right-sided damage. Patients with moderate-high activity levels performed better than patients with low activity levels on tests of spatial cognition, but both groups performed similarly on tests of verbal memory. The data therefore largely confirm the hypotheses. This is the first demonstration, within a single study, of spatial memory deficits using a virtual environment spatial navigation task in epileptic adults; and of an association between activity levels and improved spatial cognition on the CG Arena task in epileptic adults.